Effect of 5-azacytidine on mirna expression in human breast cancer cells with different sensitivity to cytostatics - Chekhun, V.F.; Borikun, T.V.; Lukianova, N.Y. (Experimental Oncology, 2016)
Aim: To analyze expression of miRNA in human breast cancer cells, sensitive and resistant to cisplatin and doxorubicin, and to explore possible modification of drug sensitivity via treatment of cells with 5-azacytidine (5-aza), a demethylating agent. Materials and Methods: The study was performed on wild-type MCF-7 cell line (MCF-7/S) and its two sublines MCF-7/Dox and MCF-7/DDP resistant to doxorubicin and cisplatin, respectively. Cells were treated with 5-aza, cisplatin, doxorubicin and their combinations. Relative expression levels of miRNA-221, -200b, -320a, -10b, -34a, -122 and -29b were examined, using qRT-PCR. The MTT assay was used to monitor cell viability. Results: We compared miRNA expression profiles in MCF-7/S and drug resistant MCF-7/Dox and MCF-7/DDP cells. Changes of miRNA-221, -200b, -320a, -10b, -34a, -122 and -29b were observed in both resistant cell lines. The most significant differences were found for miRNA-200b (decreased in 50.0 ± 2.6 and 63.0 ± 3.1 times for MCF-7/Dox and MCF7/DDP cells, respectively) and for oncogenic miRNA-221 levels (increase in 62.0 ± 5.7 times for MCF-7/Dox and 83.8 ± 7.2 times for MCF-7/DDP cells). 5-aza treatment caused an increase of miRNA-10b, -122, -200b levels in MCF-7/S cells, miRNA-34a, -10b, -122, -200b and -320a levels in MCF-7/Dox cells and miRNA-34a, -10b, -200b and -320a levels in MCF-7/DDP cells. Pretreatment of all studied lines with 5-aza resulted in the increase of their sensitivity to studied cytostatics. In particular, the IC50 of doxorubicin decreased by 2-, 4- and 3-fold for cell lines MCF-7/S, MCF-7/Dox and MCF-7/DDP cells, respectively, and IC50 of cisplatin in studied cultures decreased by 3-, 2- and 1.5-fold, respectively. Conclusions: It was shown that use of 5-aza can modify sensitivity of breast cancer cells to cytotoxic drugs not only by it’s demetylation effect, but also by changes in expression of miRNAs, involved in cell proliferation, migration and drug resistance development.